PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING METODE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI IIS 3 SMA NEGERI 1 KESAMBEN - Silky Roudhotus Sa’adah; Sapir Sapir (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2016)
This study attempts to know: (1) an increase in interest learn economic after determining model cooperative TGT and (2) increasing the study results economic after determining learning model cooperative TGT.Research approach that is used is the qualitative study is descriptive analytic. The kind of research that is used is the act of instrumen research be used that is a sheet of observation, poll, and about pretax post test and test. The subject of study class XI social scient 3 SMAN 1 Kesamben, object research cooperative TGT learning. Is using the research in 2 cycles.Study results class XI Social Scient 3 SMAN 1 Kesamben increase after done a method of learning team games tournemnt (TGT). Look increase on the outcome of post test for each cycle. On the outcome of pre test there was only one of students are be completed. Then on the outcome of post test 1 in cycle 1 the percentage rose to 41.2 %. These increases do not too large on the outcome of post test to 2 the percentage forty-seven percent only up as many as 5.8 % .But the result look significant to the test to 3 that is up from 47 % to 91.2 % the percentage the increase in 44 .2 %. Interest learn class XI Social Scient 3 SMAN 1 kesamben increased.